Enhancing Engineering Student’s Academic Performance Index through Outcome Based Education: A Case Study - Patil, Snehal S.; Patil, Sachin K.; Lokare, V. K. (Journal of Engineering Education Transformations, 2018)
Today's scenario of education goes far ahead than traditional norms for capable graduates to fulfill industry needs. Outcome-based education (OBE) has gained important recognition internationally to promote education reform and policy. Therefore, teaching -learning process need not only class based but also it emerges new technologies like e-learning, active learning. Outcome - based education means clearly focusing on what is essential for all students to be able to do successfully at the end of their learning experiences. The objective of this study compares outcome based education and traditional education (Non-OBE) with respect to Academic performance Index, which is commonly used test scores of students (Cumulative Performance index at OBE, Percentages at Non-OBE). A case study of RIT engineering education has been discussed for enhancing Academic performance Index through OBE.